2015
DOI: 10.1111/jzo.12236
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth of naturally and sexually selected traits in an Anolis lizard

Abstract: Sexual dimorphism may be indicative of differential natural and/or sexual selection pressures acting on males and females. Although similar degrees of adult sexual dimorphism may be observed among populations and species, underlying physiological, developmental and ecological processes driving growth during the juvenile stages may vary. Unraveling how and when differences arise during ontogeny is important to our understanding of the evolutionary patterns observed among adults. In addition, growth patterns may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…First, sexual selection is simply not acting on dewlap traits. This sounds highly improbable, because the dewlap has all the characteristics of a sexually secondary trait: it is highly dimorphic in adult individuals, and exhibits the typical developmental pattern with sex-specific growth trajectories once the age of maturity is reached ( Vanhooydonck et al, 2015 ). Several studies have shown that male brown anoles use their dewlap during territorial disputes ( Scott, 1984 ) and/or during courtship ( Simon, 2011 ; Driessens, Vanhooydonck & Damme, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, sexual selection is simply not acting on dewlap traits. This sounds highly improbable, because the dewlap has all the characteristics of a sexually secondary trait: it is highly dimorphic in adult individuals, and exhibits the typical developmental pattern with sex-specific growth trajectories once the age of maturity is reached ( Vanhooydonck et al, 2015 ). Several studies have shown that male brown anoles use their dewlap during territorial disputes ( Scott, 1984 ) and/or during courtship ( Simon, 2011 ; Driessens, Vanhooydonck & Damme, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Males use a conspicuous throat fan, or dewlap, as part of a visual display used to establish and maintain territories that encompass several trees (Jenssen et al, 2000;Nicholson et al, 2007;Ord, 2021;Ord et al, 2007;Ord & Stamps, 2008). The size of this dewlap in males has previously been shown to be positively correlated with bite force within species (Lailvaux & Irschick, 2007;Vanhooydonck et al, 2005) and has also been shown to be correlated with indices of sexual size dimorphism across species (Fitch & Hillis, 1984;Vanhooydonck et al, 2015). This implies male dewlap size could provide an honest indicator of potential fighting ability and reflect differences in the intensity of competition for territories among species.…”
mentioning
confidence: 99%